Altered coronary artery function, arteriogenesis and endothelial YAP signaling in postnatal hypertrophic cardiomyopathy - Langa, Paulina; Marszalek, Richard J.; Warren, Chad M.; Chowdhury, Shamim K.; Halas, Monika; Batra, Ashley; Rafael-Clyke, Koreena; Bacon, Angelie; Goldspink, Paul H.; Solaro, R. John; Wolska, Beata M. (Frontiers in Physiology, 2023)
Introduction: Hypertrophic cardiomyopathy (HCM) is a cardiovascular genetic disease caused largely by sarcomere protein mutations. Gaps in our understanding exist as to how maladaptive sarcomeric biophysical signals are transduced to intra- and extracellular compartments leading to HCM progression. To investigate early HCM progression, we focused on the onset of myofilament dysfunction during neonatal development and examined cardiac dynamics, coronary vascular structure and function, and mechano-transduction signaling in mice harboring a thin-filament HCM mutation. Methods: We studied postnatal days 7–28 (P7–P28) in transgenic (TG) TG-cTnT-R92Q and non-transgenic (NTG) mice using skinned fiber mechanics, echocardiography, biochemistry, histology, and immunohistochemistry. Results: At P7, skinned myofiber bundles exhibited an increased Ca2+-sensitivity (pCa50 TG: 5.97 ± 0.04, NTG: 5.84 ± 0.01) resulting from cTnT-R92Q expression on a background of slow skeletal (fetal) troponin I and α/β myosin heavy chain isoform expression. Despite the transition to adult isoform expressions between P7–P14, the increased Ca2+- sensitivity persisted through P28 with no apparent differences in gross morphology among TG and NTG hearts. At P7 significant diastolic dysfunction was accompanied by coronary flow perturbation (mean diastolic velocity, TG: 222.5 ± 18.81 mm/s, NTG: 338.7 ± 28.07 mm/s) along with localized fibrosis (TG: 4.36% ± 0.44%, NTG: 2.53% ± 0.47%). Increased phosphorylation of phospholamban (PLN) was also evident indicating abnormalities in Ca2+ homeostasis. By P14 there was a decline in arteriolar cross-sectional area along with an expansion of fibrosis (TG: 9.72% ± 0.73%, NTG: 2.72% ± 0.2%). In comparing mechano-transduction signaling in the coronary arteries, we uncovered an increase in endothelial YAP expression with a decrease in its nuclear to cytosolic ratio at P14 in TG hearts, which was reversed by P28. Conclusion: We conclude that those early mechanisms that presage hypertrophic remodeling in HCM include defective biophysical signals within the sarcomere that drive diastolic dysfunction, impacting coronary flow dynamics, defective arteriogenesis and fibrosis. Changes in mechano-transduction signaling between the different cellular compartments contribute to the pathogenesis of HCM.